Intention in Action The Philosophy of G. E. M. Anscombe - Rayappan, Pathiaraj; Rayappan, Pathiaraj (Peter Lang, 2010)
G. E. M. Anscombe was one of the important philosophers of the twentieth century. Her most famous works are Intention and Modern Moral Philosophy and have given origin to the new branch called Philosophy of Action and have been an impetus for the revival of Virtue Ethics. This book studies G. E. M. Anscombe$1 (Bs evaluation of moral theories and moral actions based on her findings in Philosophical Psychology. The author argues that a moral evaluation solely from the point of view of intention is insufficient and looks for a way in which this insufficiency can be overcome. Taking inspiration from Martin Rhonheimer, he finds a way to overcome this insufficiency through concepts such as the moral object, the anthropological truth of man and the practical reason, which are other essential elements to be considered in moral evaluation in addition to intention.s